การทดสอบพฤติกรรมทางโครงสร้างของรอยต่อของคานคอนกรีตอัดแรงบางส่วนสำเร็จรูป - ธำรงวุฒิ, จักษดา; แสงอาทิตย์, สิทธิชัย; คำลือ, กรรณ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2014)
บทคัดย่อ งานวิจัยนี้เป็นส่วนหนึ่งของโครงการพัฒนาคานคอนกรีตสำเร็จรูป โดยมีวัตฤประสงค์หลักเพื่อศึกษา พฤติกรรมการรับแรง และลักษณะการวิบัติของรอยต่อของคานคอนกรีตอัดแรงบางส่วนสำเร็จรูปและ คานคอนกรีตเสริมเหล็กสำเร็จรูป และนำกำลังของรอยต่อที่ทดสอบเปรียบเทียบกับค่าที่คำนวณได้จาก สมการออกแบบของ ว.ส.ท. ตัวอย่างงานวิจัยเป็นคานขนาดหน้าตัดกว้าง 0.20 m ลึก 0.40 m และมีระยะห่างระหว่างจุดรองรับ 2.0 m จำนวน 6 ตัวอย่าง ถูกทดสอบโดยแรงกระทำแบบ 3 จุด ตัวอย่างคานทั้งสองชนิดและรอยต่อได้ถูกออกแบบตามมาตรฐานของ ว.ส.ท. โดยใช้นํ้าหนักบรรทุก คงที่และนํ้าหนักบรรทุกจรทีเท่ากัน จากการทดสอบพบว่า ในช่วงแรกตัวอย่างมีพฤติกรรมรับแรง แบบเชิงเส้นถึงค่าประมาณ 75-80% ของกำลังรับแรงสูงฝืด จากนั้นตัวอย่างทดสอบจะมีพฤติกรรม แบบไร้เชิงเส้น และการแอ่นตัวมีค่าเพิ่มขึ้นอย่างรวดเร็วจนกระทั่งเกิดการวิบัติ ตัวอย่างทดสอบมีลักษณะ การวิบัติแบบ Flexural failure นอกจากนี้ยังพบว่า สมการออกแบบของ ว.ส.ท. สามารถทำนายกำลังของรอยต่อได้อย่างถูกต้องเพียงพอ คำสำคัญ : คานคอนกรีตอัดแรงสำเร็จรูป, อัดแรงบางส่วน, จุดเชื่อมต่อ Abstract This research is a part of development project on precast concrete beams. The objectives of this research are to study behaviors and modes of failure of the joints of precast partially-prestressed concrete beams and the joints of precast reinforced concrete beams, and to compare the obtained strength of the joints with those predicted by using the E.I.T. design equations. In this study, the beam specimens had the cross-sectional dimensions of 0.20x0.40 meters with the span length of 2.00 meters. The total of six specimens were tested under three-points loading. These two types of beams and the joints were designed according to E.I.T standard with the same dead loads and live loads. From the tests, it was found that the specimens have linear behavior up to 75-80% of their maximum load capacity. Then, the behavior of the specimens is nonlinear until failure. The mode of failure of all the test specimens was in the form of flexural failure. In addition, the E.I.T's design equations accurately predict the strength of the joints of the beams. Keywords : Precast Concrete Beam, Partially-Prestressed, Joint Connection